2023
DOI: 10.1186/s12866-023-02795-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lead adsorption by a Bacillus cereus strain with indole-3-acetic acid secretion and inorganic phosphorus dissolution functions

Abstract: Background Heavy metal pollution has become a major source of environmental pollution because of increasing industrialization. Microbial remediation is a promising approach to remediate lead-contaminated environments owing to its cost-effective, environment-friendly, ecologically sustainable, and highly efficient properties. In this study, the growth-promoting functions and lead-adsorption ability of Bacillus cereus SEM-15 were examined, and the functional mechanism of the strain was preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The treatment reduced Pb residue by up to 88% compared to the control; the remaining Pb residue was only 10 mg/kg (Figure 6). The low Pb residue in the soil on TSB treatment was due to B. wiedmannii adsorb Pb, as a previous study reported that B. cereus, which is closely related to B. wiedmannii can absorb Pb up to 96.58% through several mechanisms such as indole-3-acetic acid (IAA) secretion and inorganic phosphorus (P) dissolution (Miller et al 2016;Li et al 2023). Besides Pb adsorption ability, the bacterium is a biocontrol agent of the root -knot nematode (Meloidogyne arenaria) (Fallahzadeh-Mamaghani et al 2023).…”
Section: The Effect Of Pb-resistant Bacteria Inoculation On Plant Gro...mentioning
confidence: 95%
“…The treatment reduced Pb residue by up to 88% compared to the control; the remaining Pb residue was only 10 mg/kg (Figure 6). The low Pb residue in the soil on TSB treatment was due to B. wiedmannii adsorb Pb, as a previous study reported that B. cereus, which is closely related to B. wiedmannii can absorb Pb up to 96.58% through several mechanisms such as indole-3-acetic acid (IAA) secretion and inorganic phosphorus (P) dissolution (Miller et al 2016;Li et al 2023). Besides Pb adsorption ability, the bacterium is a biocontrol agent of the root -knot nematode (Meloidogyne arenaria) (Fallahzadeh-Mamaghani et al 2023).…”
Section: The Effect Of Pb-resistant Bacteria Inoculation On Plant Gro...mentioning
confidence: 95%
“…The effects of CS, CS-DA, and CS-DA-SA on the morphology of E. coli and S. aureus were observed by SEM. As described [40] with some modifications, 3 mL of bacteria in stable or late-logarithmic growth were centrifuged (8000 rpm, 5 min), and the pelleted cells were fixed in 40 volumes of 2.5% glutaraldehyde at 4 • C for a minimum of 2 h. The bacteria were washed several times in a phosphate buffer and dehydrated (50, 70, and 90% ethanol). They were then resuspended in an ethanol tert-butanol solution (1:1, v/v) for 20 min.…”
Section: Effects Of Cs-da-sa On Bacterial Morphologymentioning
confidence: 99%
“…Additionally, other species such as B. sterothemophilus, B. megaterium, B. pumilus, B. licheniformis, and B. jeotgalim have shown bioremediation capabilities [28][29][30][31], producing various secondary metabolites such as lipopeptides, polypeptides, macrolides, fatty acids, polyketides, and isocoumarins, which enable them to decontaminate soils polluted with toxic metals and organic pollutants [32]. Bacillus cereus, in particular, has been employed in various studies to break down toxic metals [33][34][35], hydrocarbons [36,37], free cyanide [38,39], pesticides [40,41], and polypropylene [42]. Given its broad applicability in bioremediation processes [43,44], unique biotechnological properties [20][21][22], involvement in the microbiota of contaminated soils, and tolerance for free cyanide, it is crucial to address the preservation of Bacillus cereus [45].…”
Section: Introductionmentioning
confidence: 99%